Effect of Ganoderma lucidum extract on tumor necrosis factor-alpha and prostaglandin E2 levels in periodontitis model Sprague Dawley rats - Andini, Restian Febi; Novrial, Dody; Widodo, Haris Budi (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Periodontitis is a chronic multifactorial disease caused by microorganisms such as G-anaerobes in the periodontal tissues. It activates host defense cells and releases inflammatory mediators such as tumor necrosis factor-alpha (TNF-α) and prostaglandin E2 (PGE2). Ganoderma lucidum is a traditional medicinal mushroom with anti-inflammatory effects against various diseases. Biologically, different levels of its active constituents, such as triterpenoids and phenolic compounds, reduce inflammation with various pathways. Furthermore, the constituents inhibit toll-like receptor 4, MyD88 receptors, and the activities of nuclear factor-kappa B, which synthesize TNF-α and PGE2. Purpose: This study aimed to analyze the extent to which G. lucidum extract can reduce TNF-α and PGE2 levels in periodontitis model Sprague Dawley rats. Methods: Thirty Sprague Dawley rats were randomly divided into six groups of five rats. Periodontitis inflammation was induced by the injection of Porphyromonas gingivalis bacteria into intrasulcular gingival incisors in the lower jaw labial section. Grouping was as follows: Group K1 (healthy control); Group K2 (negative control); Group K3 (positive control with doxycycline dose 0.27 mg/kg BW); Group P1 (G. lucidum extract dose 5 mg/kg BW); Group P2 (G. lucidum extract dose 10 mg/kg BW); and Group P3 (G. lucidum extract dose 20 mg/kg BW). Samples were taken from rat gingival tissue and the levels of TNF-α and PGE2 were examined using the enzyme-linked immunosorbent assay method. Data analysis was performed using one-way analysis of variance (ANOVA) with a confidence level of 95% (p < 0.05). Results: The levels of TNF-α and PGE2 were the highest in the K2 group and the lowest in the K1 group. One-way ANOVA showed no significant difference in TNF-α and PGE2 levels between P3 and K1 group. Conclusion: G. lucidum extract can reduce TNF-α and PGE2 levels in Sprague Dawley rats with periodontitis.